Chimeric Antigen Receptor T-Cell Therapy: Updates in Glioblastoma Treatment. Issue 6 (11th February 2021) - Feldman, Lisa; Brown, Christine; Badie, Behnam
Abstract: Glioblastoma multiforme (GBM) are the most common and among the deadliest brain tumors in adults. Current mainstay treatments are insufficient to treat this tumor, and therefore, more effective therapies are desperately needed. Immunotherapy, which takes advantage of the body's natural defense mechanism, is an exciting emerging field in neuro-oncology. Adoptive cell therapy with chimeric antigen receptor (CAR) T cells provides a treatment strategy based on using patients' own selected and genetically engineered cells that target tumor-associated antigens. These cells are harvested from patients, modified to target specific proteins expressed by the tumor, and re-introduced into the patient with the goal of destroying tumor cells. Here, we review the history of CAR T-cell therapy, and describe the characteristics of various generations of CAR T therapies, and the challenges inherent to treatment of GBM. Finally, we describe recent and current CAR T clinical trials designed to combat GBM.